THE ROLE OF THE IRAQI MEDIA IN SPREADING SPORTS CULTURE AMONG STUDENTS OF THE FACULTY OF ARTS, Department of Media, Tikrit University - Assist. Prof. Dr. Ibrahim Faisal Khalaf (Proximus Journal Publishing, 2024)
The importance of the research lies in the role played by the media in promoting sports culture among students of the Department of Media, Tikrit University As for the research problem, it was formed in terms of the researcher being from the university community and interested in this aspect and his meetings with a number of university students in general and the Department of Media in particular and the discussion that revolves around the specializations concerned with the students and the reason for their choice of study and directing some questions in the content of the specialization that the students study. He noted that there is a weakness in their possession of sports culture, which may be due to a degree to the various sports programs that do not rise to the desired level in spreading sports culture, which strengthened this view, the researcher's direction to address this study (the content of the problem)
Keywords: strengthened; culture; researcher's